STUDI FENOMENOLOGI MAKNA TRADISI BATING BAGI WARGA JEMAAT GEREJA TORAJA JEMAAT MORIA KATA KLASIS MALIMBONG - Gusti Somalinggi’ (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
A Phenomenological Study of the Meaning of the Bating Tradition for the Toraja Church Congregation, the Moria Congregation, Kata Klasis Malimbong". This thesis aims to find out the meaning of "bating" based on a phenomenological perspective and its relevance for the Toraja Church of the Moria Kata Congregation. The research method used in this study is a qualitative method using Cliffortd Geertz phenomenological approach regarding symbols in culture. Collection techniques were carried out by interview and observation techniques. Even in the bating expression that leads to the dead. However, this does not become a sign that the lamentation carried out by the community is a symbol of despair and worship of the deceased. Human nature as an image of a cultured God. This is what makes humans responsible for maintaining the culture. the task of humans is how humans can respond to the bating culture so that it can be accepted according to the gospel that focuses on worshiping only God, not on people who have died. The results of the study show that the true meaning contained in Bating is only as an emotional outlet that expresses a sign of affection for the median in which the mourner expresses all the complaints, attitudes and behavior of the median during his life